NEAT1/MALAT1/XIST/PKD–Hsa-Mir-101-3p–DLGAP5 Axis as a Novel Diagnostic and Prognostic Biomarker Associated With Immune Cell Infiltration in Bladder Cancer - Rao, Xiaosheng; Cao, Haiyan; Yu, Qingfeng; Ou, Xiuyu; Deng, Ruiqi; Huang, Jinkun (Frontiers in Genetics, 2022)
Background: The clinical value of the biomarkers of bladder cancer (BC) is limited due to their low sensitivity or specificity. As a biomarker, DLG associated protein 5 (DLGAP5) is a potential cell cycle regulator in cancer cell carcinogenesis. However, its functional part in BC remains unclear. Therefore, this study aims to identify DLGAP5 expression in BC and its potential diagnostic and prognostic values. Eventually, it predicts the possible RNA regulatory pathways of BC. Methods: Data on DLGAP5 expression levels in BC and normal bladder tissues were obtained from The Cancer Genome Atlas (TCGA) and the Gene Expression Omnibus (GEO) databases. The receiver operating characteristic (ROC), Kaplan–Meier survival curves, and the univariate and multivariate Cox regression analysis determines the diagnostic and prognostic values of DLGAP5 in BC patients. Finally, the StarBase predicted the target RNAs and constructed networks using Cytoscape. Results: DLGAP5 expression was significantly upregulated in BC tissue, verified by the TCGA (p<0.001) and GSE3167 datasets (p<0.01). BC patients with increased DLGAP5 had poor overall survival (OS) (p=0.01), disease-specific survival (DSS) (p=0.006) and progress free interval (DFI) (p=0.007). The area under the ROC curve (AUC) was 0.913. The multivariate Cox analysis identified that lymphovascular invasion (p=0.007) and DLGAP5 (p=0.002) were independent prognostic factors. Conclusion: Increased DLGAP5 expression was closely associated with a poor prognosis in BC patients. In this case, DLGAP5 might be a diagnostic and prognostic biomarker for BC. DLGAP5 expression might be regulated by NEAT1/MALAT1/XIST/PKD–Hsa-mir-101-3p pathways.